High Intensity intervals to Improve the Specific Performance of West Java Wrestlers - Erawan, Bambang; Maulana, Deris; Iskandar, Dedi (STKIP Muhammadiyah Kuningan, 2024)
Specific training methods is an important aspect in the preparation of wrestling athletes. The purpose of this study was to investigate the effect of a short-duration high-intensity interval training (HIIT) program with specific wrestling techniques on anaerobic performance. Twelve wrestling athletes were randomized into a control (n=6) or experimental groups (n=6). The experimental protocol consisted of 3 blocks of 6 sets of 10s all-out effort, with 10s passive recovery between sets and 1-min rest interval between blocks, conducted 3 days per week during 4-weeks. A three-way analysis of variance (ANOVA) (group, set and moment) with repeated measurements in the two last factors was conducted to compare the performance during each set of the Frequency Speed Kick Test (FSKT), and an ANOVA two-way (group and moment) with repeated measurements was used to compare the total number of kicks and kick decrement index (KDI). Both groups maintained their regular wrestling training, which was exactly the same. Before and after the training program the athletes performed the FSKT. The experimental group increased (p<0.01) performance in each of the five sets of the FSKT and in the total number of kicks (p<0.001). No statistical difference was observed in the control group after 4-weeks or between the control and experimental group in any moment. A short-duration HIIT program with specific wrestling techniques improved anaerobic performance measured through the FSKT. However, the fatigue index did not change.